1972
DOI: 10.1136/bmj.2.5809.352-b
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide and pigmentation.

Abstract: About 100 general practitioners on the research register of the Royal College of General Practitioners have agreed to take part in a larger study, which it is hoped will confirm these findings. This investigation is about to start, and documents to record data are being distributed. More participants will be welcome. May I, through these columns, ask interested general practitioners to write to me for further information.-I am, etc.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…Harrison, et al [5] observed the same effect in a 3-year-old boy given CyF at a dosage of 80 mg/day, and discontinued the drug because of acute hemorrhagic cystitis after one month. The pigmentation developed at the base of the finger and toe nails, and there was also a brown line on the teeth at the junction with the gums.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Harrison, et al [5] observed the same effect in a 3-year-old boy given CyF at a dosage of 80 mg/day, and discontinued the drug because of acute hemorrhagic cystitis after one month. The pigmentation developed at the base of the finger and toe nails, and there was also a brown line on the teeth at the junction with the gums.…”
mentioning
confidence: 48%
“…A blue pigmentation of fingernail is not specifically reported in company product characteristics, even if nail discoloration and nail disorders are listed among the numerous side effects, and have only anecdotally been reported in the literature [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…facial burning (6), alopecia (7-10), and hyperpigmentation (10-13) have all been observed in patients after treatment with cyclophosphamide. The hyperpigmentation is an infrequent side effect of cyciophosphamide therapy, and is generally limited to the nail beds, palms, soles, and teeth (12,13). ln one patient, however, it involved the face, neck, and arms (II).…”
Section: Discussionmentioning
confidence: 99%
“…Long term therapy with busulphan can produce a diffuse pigmentation akin to Addison's disease (Harrold, 1966). Cyclophosphamide hyperpigmentation may be widespread (Harrison & Wood, 1972) or localized to the palms soles or nails (Shah et al, 1978). Mithramycin produces hyperpigmentation in 35.% of patients on the drug whilst long term treatment with hydroxyurea induces both alopecia and pigmentation (Kennedy et al, 1975).…”
Section: Drug-induced Hyperpigmentationmentioning
confidence: 99%